The Shari ’a Rooting of the Prevailing Customs in the Kurdish Society Marriage as a Model - Dilan Mshir Ebrahim; Othman Khudhur Hamadamin (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
The rooting of Islamic laws as a systemic concept is intended to identify the Shari ‘a principles that the religious scholars and experts have come up with in their judgements; and to investigate the origin of jurisprudence on which the factual judgement is based in the Islamic juristic heritage or to judge on the emerging issues. For this, it depends on the legitimate foundations consisting of the origins and general principles and provisions of Shari ‘a law, along with juristic branches. As it is clear, customs and traditions are one of the principles of judgements and juristic evidences, in a way that these customs and traditions are considered as an intellectual legislative source depending on diligence and intellect. Moreover, Islam religion has paid great attention to family as it is reflected in the Shari ‘a provisions mentioned in the holy book of Quran, Sunnah and other sources. Furthermore, the customs and traditions have played a significant role in the family establishment and formation. In this study, we wanted to focus on marriage and the impact of the customs and traditions in implementing this contract pursuant to the Islamic Law; as these customs are common in Kurdish society along with the economic conditions that have also played a major role in this regard. In view of this in the present time, based on the changes in the customs and traditions which is intended to regulate the general life affairs and achieve the interests of the people in addition to taking into account the purposes of Shari ’a law, especially the purposes of marriage.